2008
DOI: 10.12973/ejmste/75309
|View full text |Cite
|
Sign up to set email alerts
|

“Disgusting” Animals: Primary School Children’s Attitudes and Myths of Bats and Spiders

Abstract: Knowledge of animals may influence children"s beliefs and behaviour toward them, thus building positive attitudes toward animals is one of main goals of environmental education programmes. Although keeping animals contributes to the increase of children"s positive attitudes toward wild animals, pet owners show similar negative attitudes toward less popular animals such as insects, bats or rats than non-pet owners. Moreover, some of these animals are emblazoned with various myths (hereafter alternative concepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
146
5
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(177 citation statements)
references
References 61 publications
(60 reference statements)
17
146
5
9
Order By: Relevance
“…That finding is in line of several previous studies where authors also found that interest in animals decreases over time (Prokop & Tunnicliffe, 2008;Bjerke & Østdahl, 2004, Tomažič, 2011a. Prokop et al (2007) found that Slovakian students' interest about biology decreases over years and linked their results with the topics that students learn about in different grades.…”
Section: Level Of Education and Student Attitude Ratingssupporting
confidence: 89%
See 1 more Smart Citation
“…That finding is in line of several previous studies where authors also found that interest in animals decreases over time (Prokop & Tunnicliffe, 2008;Bjerke & Østdahl, 2004, Tomažič, 2011a. Prokop et al (2007) found that Slovakian students' interest about biology decreases over years and linked their results with the topics that students learn about in different grades.…”
Section: Level Of Education and Student Attitude Ratingssupporting
confidence: 89%
“…Species that are usually used in attitude research are either charismatic or flagship species such as dolphins (Barney et al, 2005), primates (Lukas & Ross, 2005), or large carnivores (Majic & Bath, 2010;Prokop, Usak & Erdogan, 2011). One branch of research is about attitudes toward animals that people dislike or fear, like sharks (Thompson & Mintzes, 2002), crows (Špur, Pokorny & Šorgo, 2016), snakes, spiders, and bats (Prokop & Tunnicliffe, 2008Prokop et al, 2009) was conducted. However, attitudes toward amphibians had been, with few exceptions, scarcely researched (Randler et al, 2005;Tomažič, 2008;Tomažič, 2011a;Prokop & Fančovičová, 2012;Reimer et al, 2014;Jimenez & Lindemann-Matthies, 2015a;Jimenez & Lindemann-Matthies, 2015b).…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 99%
“…Previous research also indicates that the depiction of animals is a common attribute of young children's representations of nature [28][29][30]. In addition, it has also been reported that invertebrates may appear in young children's representations of the environment even though this group of animals tend to be misrepresented [31].…”
Section: Discussionmentioning
confidence: 99%
“…Prokop and Tunnicliffe (2008) found a positive association between knowledge of and attitudes toward animals less associated with people's phobias (such as bats), but no similar relationship between knowledge of and attitudes toward animals more associated with phobias (such as spiders). The authors speculate that public awareness is simply unable to improve attitudes toward animals that were associated with danger in human evolutionary history.…”
Section: Contribution Of This Paper To the Literaturementioning
confidence: 76%
“…But in recent years, such studies are also turning to animals such as bats, spiders, snakes (Prokop & Tunnicliffe, 2008, 2010Prokop et al, 2009a,b) and amphibians (Randler et al 2005, Tomažič, 2008. All of the mentioned studies encompass both formal and informal aspects of education as their integral feature.…”
mentioning
confidence: 99%